ISOMORPHIC TRANSFORMATION AND ITS APPLICATION TO THE MODULO (2^n+1) CHANNEL FOR RNS BASED FIR FILTER DESIGN - Stamenković, Negovan (Bulletin of Natural Sciences Research, 2019)
In this paper, the implementation of a Finite Impulse Response (FIR) filter in the Residue Number System (RNS), is presented, in which a modulo multiplier based on the isomorphism technique is used to perform multiplication in the (2n+1) channel. An RNS modular multiplication in the Galois Field GF(2n+1) is presented in detail in this paper. The multiplication is based on the isomorphic mapping technique adapted to the residue arithmetic. The isomorphic encoder and decoder look-up tables in the GF(28+1) are given. An architecture for FIR filter design based on distributed arithmetic for multiplication and accumulation in mentioned (2n+1) channel is also presented. This architecture is discussed in details and compared with with architecture based on isomorphing technique.